2021
DOI: 10.1371/journal.pone.0259998
|View full text |Cite
|
Sign up to set email alerts
|

Black raspberry restores the expression of the tumor suppressor p120ctn in the oral cavity of mice treated with the carcinogen dibenzo[a,l]pyrene diol epoxide

Abstract: One of the major risk factors for head and neck squamous cell carcinoma (HNSCC) is tobacco smoke exposure, but the mechanisms that can account for disease development remain to be fully defined. Utilizing our HNSCC mouse model, we analyzed oral squamous cell carcinomas (OSCC) induced by the active metabolite of a common smoke constituent, dibenzo[a,l]pyrene diol-epoxide (DBPDE). Analyzing protein expression by either immunofluorescence or immunohistochemistry, we identified biologic processes that are dysregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…10,11 Therefore, in a series of previous studies, we reported that BRB inhibits DBP-induced DNA damage, mutagenesis and OSCC development. 12,13 We also showed that BRB enhanced the DNA repair capacity of DNA damage induced by DBP 14 and altered genetic 15 and epigenetic markers 16 in a manner consistent with its cancer prevention activity.…”
Section: ■ Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…10,11 Therefore, in a series of previous studies, we reported that BRB inhibits DBP-induced DNA damage, mutagenesis and OSCC development. 12,13 We also showed that BRB enhanced the DNA repair capacity of DNA damage induced by DBP 14 and altered genetic 15 and epigenetic markers 16 in a manner consistent with its cancer prevention activity.…”
Section: ■ Introductionsupporting
confidence: 57%
“…DBPDE-N 6 -dA and its isotope-labeled [ 15 N 5 ]DBPDE-N 6 -dA adduct standards were prepared as previously reported. 25 [ 13 C 4 , 15 N 2 ]GSSG ammonium salt was obtained from Toronto Research Chemical, Inc. (North York, Ontario, Canada). [ 13 C 2 , 15 N]GSH trifluoroacetate salt was obtained from Sigma-Aldrich (St. Louis, MO).…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Although tumors that arise from this model make extensive functional characterization of immune cell populations in the tumor microenvironment technically challenging, it remains one of the best models that mimic the stepwise progression observed in HNSCC patients. Using these and other related animal models, we and others have demonstrated the chemopreventive potential of BRB in HNSCC chemoprevention ( 10 , 27 , 29 , 30 ). While multiple mechanisms have been proposed to mediate HNSCC chemoprevention, including modulation of tumor suppressor and apoptotic genes, as well as proinflammatory, glycolytic, and glucocorticoid signaling pathways ( 27 , 29 31 ), modulation of adaptive immune cells in a manner that promotes tumor cell cytotoxicity in the tumor microenvironment is a novel and potentially major mechanism of HNSCC chemoprevention by BRB.…”
Section: Discussionmentioning
confidence: 85%